2018
DOI: 10.3390/su10061916
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Power Transmission Bottlenecks into Aggregated Energy System Models

Abstract: Abstract:Energy scenario analyses are able to provide insights into the future and possible strategies for coping with challenges such as the integration of renewable energy sources. The models used for analyzing and developing future energy systems must be simplified, e.g., due to computational constraints. Therefore, grid-related effects and regional differences are often ignored. We tackle this issue by presenting a new methodology for aggregating spatially highly resolved transmission grid information for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The analyses for this study were conducted with two model setups which were partially extended. Although most of our analyses are performed for both of them, the results presented in Section 4 build on the REMix instance presented in [77]. The corresponding LP represents the German power system for an energy scenario of the year 2030.…”
Section: Modeling Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses for this study were conducted with two model setups which were partially extended. Although most of our analyses are performed for both of them, the results presented in Section 4 build on the REMix instance presented in [77]. The corresponding LP represents the German power system for an energy scenario of the year 2030.…”
Section: Modeling Setupmentioning
confidence: 99%
“…where: η e : fuel specific emissions and m: maximal emissions. In preliminary experiments resulting from a broad spectrum of REMix applications, ranging from country specific cross-sectoral energy systems [86,87] to multi-regional [85,[88][89][90] and spatially highly resolved power systems [77], for monolithic LPs, we observed the best performance in terms of computing time and RAM requirements with the following solver parameters when using CPLEX:…”
Section: Characteristic Constraintsmentioning
confidence: 99%
“…More precisely, to plan energy systems, we use an advanced ESOM called the "Renewable Energy Mix for a sustainable energy supply" (REMix). Today's applications range from country-specific cross-sectoral energy system analyses (Gils et al, 2017b) to multi-regional powersystem analyses of high spatial resolution (Cao et al, 2018). The modeling approach and the essential functionalities of the model are described in Gils et al (2017a).…”
Section: Methodsmentioning
confidence: 99%
“…Kies et al [14] for instance found that insufficient transmission capacities might cause large amounts of renewable generation to be curtailed. Consequently, Cao et al * corresponding author: Bruno Schyska (bruno.schyska@dlr.de) [15] suggested to incorporate transmission bottlenecks directly into energy system models. Similar to the optimal mix of generation sources, there is a well-known interaction between transmission and storage [16].…”
Section: Introductionmentioning
confidence: 99%